2006
DOI: 10.1128/aem.01047-06
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Chilling Resistance of Inoculated Grapevine Plantlets with a Plant Growth-Promoting Rhizobacterium,Burkholderia phytofirmansStrain PsJN

Abstract: In vitro inoculation of Vitis vinifera L. cv. Chardonnay explants with a plant growth-promoting rhizobacterium, Burkholderia phytofirmans strain PsJN, increased grapevine growth and physiological activity at a low temperature. There was a relationship between endophytic bacterial colonization of the grapevine plantlets and their growth at both ambient (26°C) and low (4°C) temperatures and their sensitivities to chilling. The major benefits of bacterization were observed on root growth (11.8-and 10.7-fold incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
256
0
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 506 publications
(278 citation statements)
references
References 42 publications
17
256
0
5
Order By: Relevance
“…In addition, insecticidal activities were reported for some PGPB in addition to the existing biocontrol repertoire with perspectives for application against insect crop pests [48]. Recent reports suggest that PGPB also enhance the tolerance of plants towards abiotic stresses such as drought [54,58], chilling injury [3], salinity [22], metal toxicity [13] and elevated temperature stress [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, insecticidal activities were reported for some PGPB in addition to the existing biocontrol repertoire with perspectives for application against insect crop pests [48]. Recent reports suggest that PGPB also enhance the tolerance of plants towards abiotic stresses such as drought [54,58], chilling injury [3], salinity [22], metal toxicity [13] and elevated temperature stress [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The augmented content of total phenols in roots of treated cuttings is of notable importance considering the prominent role of these compounds in the enhancement of plant defence [10,28,29]. Several authors have reported the effects of systemic resistance induced through PGPRs in different crops, including grapevines, and it has been associated with the enhancement of plant defence.…”
Section: Discussionmentioning
confidence: 99%
“…The root biomass was evaluated by fresh and dry weight (held at 65°C until reaching constant weight). Moreover, samples of roots were processed in order to determine the content of: total phenolic compounds in fresh material (0.6 g), according to Ait Barka et al [10]; content of main mineral macro-elements (N, P, K) and the micro-element Fe in ashes (0.5 g of dried material heated to 600°C for 14 hours), according to Sabir et al [7]. Chemical analyses were performed at least in triplicate both in control and treated cuttings.…”
Section: Methodsmentioning
confidence: 99%
“…Last decade saw an explosion of publications reporting the benefi cial effects of microorganisms such as Pseudomonas, Bacillus, Arthrobacter, Pantoea, Burkholderia, Rhizobium etc. in enhancing the tolerance of crops such as sunfl ower, maize, wheat, chickpea, groundnut, spices and grapes to drought, salinity, heat stress and chilling injury under controlled conditions [3,4]. The introduced microorganisms in the rhizosphere enhance soil aggregation by production of EPS thereby improving the water availability to plants during dry periods [5], induce the synthesis of heat shock proteins and osmoregulants such as proline, glycine betaine, help in maintenance of cell membrane integrity [6], all of which contribute to improved stress tolerance in plants.…”
mentioning
confidence: 99%